The constitutional validity of section 78(1B) of the Criminal Procedure Act 51 of 1977 with regard to section 9 of the Constitution of the Republic of South Africa, 1996 - Carstens, Pieter Albert, 1960- (University of Pretoria, 2013)
Dissertation (LLM)--University of Pretoria, 2012.